2014
DOI: 10.4236/ojd.2014.31006
|View full text |Cite
|
Sign up to set email alerts
|

Association between Depression and Social Demographic Factors in a Nigerian Family Practice Setting

Abstract: Objectives: Although depression is one of the more common illnesses in outpatients' clinic, it is often overlooked. Besides accurate identification and treatment is challenging. As pertinent as demographic factors are in explaining the variability of depressive symptoms, there is paucity of data in Nigeria in particular, and West Africa in general, hence the need to bring into lime light the association between depression symptoms and socio-demographic factors in a General Outpatients Clinic in Nigeria, West A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
13
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 21 publications
6
13
4
Order By: Relevance
“…This is somewhat similar to another study done in Ilorin, North Central Nigeria, which recorded a strong statistical association between depression and age group, sex, marital status, level of education, occupation, and monthly income. However, religion and ethnicity had no statistically significant relationship with depression in this study (Shittu et al, 2014).…”
Section: Introductioncontrasting
confidence: 69%
See 1 more Smart Citation
“…This is somewhat similar to another study done in Ilorin, North Central Nigeria, which recorded a strong statistical association between depression and age group, sex, marital status, level of education, occupation, and monthly income. However, religion and ethnicity had no statistically significant relationship with depression in this study (Shittu et al, 2014).…”
Section: Introductioncontrasting
confidence: 69%
“…Relationship between socio-demographic factors and depression among preand post-menopausal women. which found a significant association between marital status, age, educational level and depression prevalence in women (Salihu & Udofia, 2016;Shittu et al, 2014). Worthy of note, however, is the fact that the older women in both age groups were more prone to having depression; that the widowed pre-menopausal and married post-menopausal women had increased depression prevalence; and that in both groups, lack of formal education was associated with greater depression prevalence.…”
Section: Discussionmentioning
confidence: 92%
“…Women are more likely to experience depression than men and it has been shown that one third of women will experience a major depressive episode in their lifetime [2,4,5]. Factors that play a role in the etiology and clinical manifestation of depression include biochemistry, genetics, personality, environmental factors amongst others.…”
Section: Introductionmentioning
confidence: 99%
“…There is abundant evidence that sleep problems can account for or conversely can be explained by various emotional disturbances, including anxiety (e.g., Fite, Becker, Rubens, & Cheatham-Johnson, 2015;Iwadare et al, 2015;Leblanc, Desjardins, & Desgagné, 2015;Weiner, Meredith Elkins, Pincus, & Comer, 2015), depression (e.g., Shittu et al, 2014;Sivertsen, Harvey, Lundervold, & Hysing, 2014;Zuo, McCabe, Mellor, & Xu, 2015), and anger or aggression (e.g., Fite et al, 2015;Ireland & Culpin, 2006;Vaughn, Salas-Wright, White, & Kremer, 2015). The presence of insomnia or hypersomnia is indeed a diagnostic criterion for mood disorders, including both major depression and bipolar disorders (American Psychiatric Association, 2013).…”
Section: Introductionmentioning
confidence: 99%